Papillary-Type Carcinoma of the Thyroglossal Duct Cyst: The Case for Conservative Management. (October 2018) - Wood, C. Burton; Bigcas, Jo-Lawrence; Alava, Ibrahim; Bischoff, Lindsay; Langerman, Alexander; Kim, Young
Objectives: Thyroglossal duct cyst (TGDC) is the most common congenital neck mass, presenting in up to 7% of the population. TGDC carcinoma is much less common, occurring in roughly 1% of patients diagnosed with TGDC. The vast majority of these tumors are papillary-type thyroid cancer. Given its rarity, there is wide variation in management recommendations for this disease. Extent of surgical management and need for adjuvant therapy including radioactive iodine ablation (RAI) are particularly debated, with some authors arguing aggressive therapy including RAI for any patients who undergo concurrent thyroidectomy with the Sistrunk procedure for TGDC carcinoma. We present a series of patients treated for TGDC carcinoma at our institutions and discuss our management algorithm. Methods: This is a retrospective chart review of patients with TGDC treated at 2 separate institutions. Factors reviewed included patient age, sex, preoperative diagnosis, preoperative work-up, extent of therapy, and use of adjuvant therapy. Results: Six patients who were treated for TGDC carcinoma at our institutions were identified. One patient was excluded because the patient had been treated at an outside facility prior to referral. All patients had papillary-type thyroid cancer. One patient underwent the Sistrunk procedure alone, and the remaining 4 underwent the Sistrunk procedure plus total thyroidectomy. Two of 4 patients were noted to have malignancy in the thyroid. Two of 4 patients who underwent thyroidectomy additionally received adjuvant RAI. Conclusion: Thyroglossal duct cyst carcinoma is uncommon and management is controversial. In low-risk patients (single tumor focus, negative margins, normal preoperative neck/thyroid imaging, no extension of TGDC carcinoma beyond the cyst wall), the Sistrunk procedure alone with observation of the thyroid may be sufficient. In this patient population, RAI is unlikely to be of any substantial benefit.